Kawasaki Disease Complicated by Salmonella oranienburg Coinfection. (2nd April 2021) - Barbara, Zachary; Ellenwood, Savannah P.; Loe, Emily D.; Choi, Joon; Ryan, Kathleen; Joseph, Nancy
Abstract : Kawasaki disease is a medium vessel vasculitis with a multisystem presentation affecting 9–20 per 100, 000 children under 5 years of age in the United States. Salmonella coinfection has not been previously described. We present a 12-month-old vaccinated male with Kawasaki disease in the setting of Salmonella bacteremia. Initial intervention for the Kawasaki disease with IVIG was ineffective, prompting adjunctive therapy with anakinra, with eventual full recovery. Concurrent Kawasaki disease and bacteremia may confound diagnosis and necessitate nontraditional treatment approaches.